2011
DOI: 10.1515/bc.2011.038
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 controls matrix metalloproteinase-1 expression in colon carcinoma cells by both direct and AP-1-mediated interaction with the MMP-1 promoter

Abstract: Aberrant activation of STAT3 in colorectal carcinoma (CRC) tissue is correlated with elevated expression of matrix metalloproteinase-1 (MMP-1). We analyzed transcriptional regulation of the human MMP-1 promoter in CRC cells by tyrosine phosphorylated (pY-) STAT3. One of six putative STAT binding elements within a 4.3 kb MMP-1 trancriptional promoter fragment showed a particular high affinity for STAT3 in vitro. However, the most profound regulatory influence on MMP-1 promoter activity resides in a proximal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 32 publications
6
45
0
Order By: Relevance
“…Matrix metalloproteinase 1 (MMP-1) is associated with lung cancer growth and invasiveness [34], and STAT3 aberrantly induces the MMP-1 gene in colorectal carcinomas [35]. An assay with the MMP1 promoter placed in front of luciferase revealed that increasing amounts of SIAH2 repressed the activity of this reporter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Matrix metalloproteinase 1 (MMP-1) is associated with lung cancer growth and invasiveness [34], and STAT3 aberrantly induces the MMP-1 gene in colorectal carcinomas [35]. An assay with the MMP1 promoter placed in front of luciferase revealed that increasing amounts of SIAH2 repressed the activity of this reporter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The matrix metalloproteinase (MMP) family of proteases are zinc-dependent and are capable of degrading many types of extracellular matrix proteins and several family members are confirmed STAT3 target genes. MMP-1 was observed to be up regulated in a STAT3-dependent manner in human colorectal adenocarcinoma and urinary bladder transitional cell carcinoma cells [50,113]. The MMP1 gene was found to contain a STAT3 and an AP-1 binding site and mutation of either the STAT3 or AP-1 site ablated STAT3-mediated gene activation [50,113].…”
Section: Tumor Supporting Functions Of Stat3mentioning
confidence: 99%
“…MMP-1 was observed to be up regulated in a STAT3-dependent manner in human colorectal adenocarcinoma and urinary bladder transitional cell carcinoma cells [50,113]. The MMP1 gene was found to contain a STAT3 and an AP-1 binding site and mutation of either the STAT3 or AP-1 site ablated STAT3-mediated gene activation [50,113]. Further investigation revealed both STAT3 and c-Jun were directly bound to the MMP1 promoter in a manner dependent on c-Jun binding [50].…”
Section: Tumor Supporting Functions Of Stat3mentioning
confidence: 99%
“…STAT3 regulates the transcription of MMP-1, which has been reported in colon cancer. STAT3 may directly act on MMP-1 or indirectly facilitate MMP-1 expression via activator protein (AP)-1 (a transcription factor) (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 may also facilitate the expression of matrix metalloproteinase (MMP) family members, including MMP-2 (9), MMP-7 (10) and MMP-9 (6), which have crucial roles in the invasion and metastasis of GC. There is evidence indicating that the expression of STAT3 and MMP-1 is increased in colon cancer, which exerts a promotive effect on the invasion and metastasis of GC (11,12). Studies have also demonstrated increased MMP-1 levels in peripheral blood in GC patients and elevated MMP-1 expression in GC tissues (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%